Pegaruh Motivasi, Disiplin dan Kemampuan Mengajar Terhadap Kinerja Guru SMA N di Kabupaten Empat Lawang - Hariansyah, Adi; Syahri, Indawan; Asiati, Diah Isnaini (MOTIVASI, 2019)
ABSTRACT Purpose - The purpose of this research is to find out how the Effect of Motivation, Discipline and Teaching Ability on the Performance of High School Teachers in the District of Four Lawang.Design/methodology - The design of this study is associative research using a causal relationship. The data used in this study are primary data from the answers of respondents as many as 107 teachers of Public High Schools in Empat Lawang Regency. The analytical method used is multiple linear regression and through testing validity and reliability. Test the data used to determine the characteristics of the data, namely the normality test and linearity test. The model test used consisted of multicollinearity test and heteroscedasticity test.Findings - The results of multiple linear regression testing showed motivation, discipline, and ability together to have a significant effect on teacher performance. Partially motivation has a positive and significant effect on teacher performance, discipline has a positive and significant effect on teacher performance, ability has a positive and significant effect on teacher performance.